IN HOUSE TRAINING UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MENYUSUN RPP - Jayadipura, Yadi (Idaarah: Jurnal Manajemen Pendidikan, 2018)
Abstract: This study aims to determine the increase in teacher competency at SMPN 2 Tempuran, Kabupaten Karawang in compiling plans for implementing learning through IHT activities. The subjects of this study were all PNS teacher in SMPN 2 Tempuran Kabupaten Karawang. This research is School Action Research (PTS) which consists of two cycles, each cycle covering the stages of planning, implementation, observation and reflection. The data analysis technique used is descriptive comparative. From the results of the study it can be concluded that: IHT can improve the professional competence of teachers at SMPN 2 Tempuran in preparing lesson plans. This is indicated by the increasing professional competence of teachers from the preparation stage to the end of Cycle II.